Anaerobic Co-digestion of Organic Residues from Different Productive Sectors in Colombia: Biomethanation Potential Assessment (2016)
The residues enriched in putrescible materials and those with a high content of organic fraction produce large environmental impacts and other problems associated with the productive sector where they are generated. Colombia has a high biomass potential susceptible to be energetically valorized through biological processes achieving two functions: treatment and energy production. Anaerobic digestion is established as a technology with worldwide applications inside the circular biobased economy concept (cradle to cradle). Nevertheless, most of the studies related to technologies like anaerobic digestion have been concentrated on residues from industrialized countries. Considering the variability of residues composition depending on the level of development of a country, it is necessary to assess the biomethanation potential of biomass produced by different productive sectors in Colombia. In this study, a biomethanation potential assessment of organic residues (Organic Fraction of Municipal Solid Wastes, swine manure, cocoa husks and pods, residues from the bottled fruit drinks industry and rice stovers) from different productive sectors in Colombia was carried out. The biochemical methane potential (BMP) of each residue and its mixtures was carried out in a system which consisted in a battery of batch reactors (250 and 120 mL bottles) equipped with gasometers. To keep mesophilic conditions, an immersion thermostated bath was used. For all mixtures, an optimum C/N ratio of 20-30 was fixed based on the previous physicochemical characterization of the employed residues. The batch digestion process was evaluated until the total stoppage of gas production. The results indicate that the best mixture in terms of biogas production is the one containing cocoa, fruits and swine manure (C/N = 24), reporting a cumulative specific gas production around 497 mL CH4/